Untrol: Post-Truth and the New Normal of Post-Normal Science (2020)
The idea that there exists a natural relationship between intellectual freedom, legitimate political authority and enjoyment of a dignified life was central to the European Enlightenment and to the radical social change it inspired. This normative claim was rooted in an epistemological proposition: truth is not revealed in private to a select few but discovered in public, through observation, dialogue and critique. Material transformations associated with that proposition have since literally changed the face of the earth. While the materially transformative potential of this proposition has been realized across the planet, its social justice implications have not. This leaves an underdetermined space in democratic discourse: fact claims are treated as apolitical, while the causes and consequences of the Anthropocene are uncertain and values regarding its importance polarised, rendering that status obsolete. In addition to contributing toward understanding human-environment relationships, fact now also serve to destabilize political discourse. Their instrumentalization exerts control in the absence of normative intention, ‘untrol’: truth claims matter not only because they call the moral subject to action but also because they can proffer political standing. Humbly embracing the epistemological complexity of the Anthropocene through Eagleton’s posture of ‘hope without optimism’ is proposed as an antidote. © 2020, © 2020 Informa UK Limited, trading as Taylor and Francis Group.